Cultural persistence of self-assessed health: A study of first- and second-generation migrants - Joan Costa-Font; Azusa Sato; Belen Saenz-de-Miera (Journal of Migration and Health)
Objectives: We measure the cultural persistence of health assessments; namely the association between first (and second) generation migrants' health assessments and those of their home country (and that of their parents). Measure: We use individual data records from over thirty host European countries and over ninety sending countries, as well as controls for migration timing and legal citizenship status. Furthermore, we leverage a wide range of sample countries to attenuate the presence of selection bias. Results: Our estimates document evidence of cultural persistence of health self-assessments in a wide array of different specifications which vary with age. We estimate that a one standard deviation change in self-reported health in the sendning country is associated with an increase in migrants’ self-reported health of about 0.17 standard deviations. The effect size is sensitive to the inclusion of country of residence fixed effects as well as the presence of selection on observables and other robustness checks. Conclusion: Cross-country comparisons of self-reported health should consider cultural reference points individuals use in assessing their health.